2020
DOI: 10.1177/0898264320984016
|View full text |Cite
|
Sign up to set email alerts
|

Love thy Aged? A State-Level Analysis of Religiosity and Mobility in Aging Populations During the Novel Coronavirus (COVID-19) Pandemic

Abstract: Objectives: We test whether the association between state religiosity and distance traveled is moderated by population age during the novel coronavirus (COVID-19) pandemic. Methods: Mobility is operationalized as the state-level average median distance traveled from February 24 to May 4 across the contiguous United States. Shelter-in-place rates are operationalized as the state-level percentage of users staying home. State religiosity is measured with an index of aggregated religious identities, beliefs, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Certain religious populations may also resist public health recommendations and the adoption of healthy pandemic lifestyles because they tend to hold more negative views of science and scientists and strong religious beliefs concerning the pandemic (Hill, Gonzalez, & Burdette, 2020;Hill, Gonzalez, & Upenieks, 2021;Perry, Whitehead, & Grubbs, 2020). Several studies show that more religious populations tend to report less trust in science as a social institution and more anti-science attitudes (Evans, 2013;Gauchat, 2008Gauchat, , 2012.…”
Section: Pillar 2: Conservative Protestantismmentioning
confidence: 99%
“…Certain religious populations may also resist public health recommendations and the adoption of healthy pandemic lifestyles because they tend to hold more negative views of science and scientists and strong religious beliefs concerning the pandemic (Hill, Gonzalez, & Burdette, 2020;Hill, Gonzalez, & Upenieks, 2021;Perry, Whitehead, & Grubbs, 2020). Several studies show that more religious populations tend to report less trust in science as a social institution and more anti-science attitudes (Evans, 2013;Gauchat, 2008Gauchat, , 2012.…”
Section: Pillar 2: Conservative Protestantismmentioning
confidence: 99%
“…Researchers found that religious conservatives and devoutly religious people and places with higher numbers of them were less likely to wear masks, social distance, or comply with stay-at-home orders (Adler Jr et al, 2021 ; Corcoran et al, 2022 ; Gonzalez et al, 2021 ; Hill et al, 2020 , 2021 ; Perry et al, 2020a ; Pew Research Center, 2020 ; Scheitle & Corcoran, 2021 ; Schnabel & Schieman, 2022 ). Surveys fielded in March and June 2020 indicated that white evangelical Protestants in the USA were among the least likely to comply with these policies and the most likely to support the restrictions’ termination (Pew Research Center, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Christian nationalists (i.e., those who ascribe to a politically infused conservative religious ideology) were particularly resistant to COVID-19 mandates viewing them as contrary to economic prosperity and liberty (Perry et al, 2020a , 2020b ). This resistance was likely also rooted in cultural distrust of medicine, the government, and science (Armer & Radina, 2006 ; Baker et al, 2020 ; Galanter, 1999 ; Gastañaduy et al, 2016 ; Glassman, 2018 ; Gonzalez et al, 2021 ; Hill et al, 2020 , 2021 ; Miller & Karkazis, 2013 ; Offit, 2015 ; Stein et al, 2022 ; Thompson & Kisjes, 2016 ; Whitehead & Perry, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the U.S., religiosity has been an influential factor in the misinformation generated about COVID-19 ( Bentzen, 2020 ; Hill, Gonzalez, & Upenieks, 2021 ). Religious affiliation related to greater disregard to shelter-in-place guidelines to remain at home ( Hill et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the U.S., religiosity has been an influential factor in the misinformation generated about COVID-19 ( Bentzen, 2020 ; Hill, Gonzalez, & Upenieks, 2021 ). Religious affiliation related to greater disregard to shelter-in-place guidelines to remain at home ( Hill et al, 2021 ). Biblical literalist conservative Protestants studied from 1984 to 2010 increasingly opposed scientists on moral and social issues ( Evans, 2013 ).…”
Section: Introductionmentioning
confidence: 99%